Military physical training-related injuries: A review of epidemiology and risk factor and prevention strategy studies - M Zarei; M Rahemi (فصلنامه ابن سینا)
Background: Musculoskeletal physical training-related injuries are a major problem in military populations. Preventing training–related injuries would reduce associated human and economic costs and discharges from the army. Identification of injury rates, injury type and location and risk factors for military populations for such injuries is a crucial step toward their prevention. Thus this study reviews pertinent epidemiologic literature on musculoskeletal injury for military populations. Materials and methods: Original studies about injuries in military populations published since 1990 in peer-reviewed journals were identified using PubMed, Web of Science, and Google Scholar databases. This search was last performed in May 2015. Results: Injury rates during military training are high, ranging from 6 to 12 per 100 male recruits per month during basic training to as high as 30 per 100 per month. Data collected show low levels of current physical fitness, high running mileage, high amount of weekly exercise, smoking, age, and biomechanical factors are among the most important risk factors in military injuries. Also Education, prevent overtraining, agility-like training, mouth-guards, semi-rigid ankle braces, nutrient replacement, and synthetic socks were determined to be critical components of any successful injury prevention program. Conclusion: Given the size of the problem, identify risk factors for military populations are critical component for prevention.